2020
DOI: 10.1021/acsomega.9b03761
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Gum Arabic/κ-Carrageenan-Incorporated Nano-Hydroxyapatite Nanocomposites and Their Relative Biological Functionalities in Bone Tissue Engineering

Abstract: The present frontiers of bone tissue engineering are being pushed by novel biomaterials that exhibit phenomenal biocompatibility and adequate mechanical strength. In this work, we fabricated a ternary system incorporating nano-hydroxyapatite (n-HA)/gum arabic (GA)/κ-carrageenan (κ-CG) with varying concentrations, i.e., 60/30/10 (CHG1), 60/20/20 (CHG2), and 60/10/30 (CHG3). A binary system with n-HA and GA was also prepared with a ratio of 60/40 (HG) and compared with the ternary system. A rapid mineralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 66 publications
(104 reference statements)
0
21
0
Order By: Relevance
“…This may be attributed to the presence of higher amount of CG in the hydrogels. It has been established that CG is responsible for higher Ca deposition because of its affinity to bind Ca that subsequently accelerate cell differentiation giving rise to new bone formation [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be attributed to the presence of higher amount of CG in the hydrogels. It has been established that CG is responsible for higher Ca deposition because of its affinity to bind Ca that subsequently accelerate cell differentiation giving rise to new bone formation [17].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the gel strength has been found to be higher in case of less sulfate concentration in carrageenan and the least ester sulfate is available in κ-carrageenan that can be most appropriate for applications in bone scaffolds. In addition, GAGs which are the constituent of bone and cartilage of humans have been shown to have structurally analogous to κ-carrageenan (κ-CG) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Kappa‐carrageenan is a gelling agent processed from a natural sea‐weed source. They have been studied in vitro, showing promising levels of osteogenesis and cytocompatibility 178,179 . Injectable composites made of tricalcium phosphate substituted with magnesium mixed with calcium sulfate hemihydrate particles, which had self‐setting ability, were tested in vivo in beagle condyle defects exhibiting new bone formation, biodegradability, and biocompatibility 180 .…”
Section: Classificationmentioning
confidence: 99%
“…Comparative assessment of morphological, physicochemical, and biological studies revealed that ternary systems possess superior biocompatibility, protein adsorption and osteogenic protein expression as compared to the binary system formed by nHA and GA. Therefore, the authors concluded that the incorporation of kappa -CG to the ternary system outperforms the binary system collectively in terms of bioactivity with the maximal activity shown by the nanocomposite formed by nHA/GA/ kappa -CG in a ratio of 60/20/20 [ 192 ].…”
Section: Carrageenan In Biomedical Applicationsmentioning
confidence: 99%